Identifikasi Waste Defect Type 2 Dengan Pendekatan Metode Lean Manufacturing Untuk Meminimalisir Cacat Produksi pada ProsesTurning di CV. ABC - Hamidah, Nur; Sulistyowati, Enik; Riyana, Iis (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
CV. ABC is a wood-processing manufacturing company with one of its main products being turning components. The primary issue faced by the company is waste caused by frequent product defects due to human error. This study aims to minimize non-value-added activities and identify the root causes of human error in the turning production process. The Value Stream Mapping (VSM) method is used to map the process flow from raw materials to finished products. Data were collected through questionnaires and analyzed using WAM, WRM, and WAQ. The results identified the three highest types of waste: defect (27.979%), overproduction (15.471%), and inventory (12.363%). Waste prioritization was carried out using VALSAT, with PAM and QFM selected as the most influential tools. Fishbone analysis revealed lack of focus and attention to detail as the main causes of human error. Improvements were proposed through skill enhancement training, occupational health and safety (OHS) implementation, and regular checklist usage. As a result, processing time was reduced from 2,384.2 minutes to 2,247.4 minutes, as illustrated in the Future State VSM.